(untitled) (Iranian Journal of Kidney Diseases, 2022)
Introduction. Patients with β -thalassemia major (β -TM) had a high rate of glomerular dysfunction due to chronic anemia, iron overload, and chelation therapy. There is also evidence of proximal tubular damage, as almost all patients have various amounts of proteinuria. MicroRNAs are non-coding RNA molecules that regulate gene expression. In diabetes, a relative increase in renal microRNA-451 appeared to protect against diabetic kidney injury. This study aimed to investigate the association between miRNA-451 and the development of chronic kidney disease (CKD) in children with β-TM. Methods. This study included 60 pediatric patients with β-TM and 30 healthy children as controls. We categorized patients into two groups according to the presence of CKD. Complete blood and reticulocyte counts, serum levels of ferritin, creatinine and glucose, and urine albumin/creatinine ratio (ACR) were measured. Plasma miRNA-451 expression level was measured by real-time quantitative reversed transcription PCR in all included children. Results. miRNA-451 levels were significantly higher in β-TM (25.326 ± 12.191) as compared with controls (9.453 ± 5.753) (P < .001). Patients with β-TM and CKD had significantly lower miRNA-451 levels (19.72 ± 13.023) than those without CKD (30.933 ± 8.23). MiRNA-451 levels had significantly positive correlated with eGFR (r = 0.385 P < .05) and reticulocyte counts (r = 0.27, P < .05). Linear logistic regression analysis showed that low plasma microRNA-451 was a significant independent predictor of CKD. Conclusion. miRNA-451 has a protective role against CKD development, and low plasma expression levels are associated with CKD in children with β-TM DOI: 10.52547/ijkd.6756